Coronaries from the Brachiocephalic Artery: Anomalous Origin of the Coronary Arteries in a Case of Situs Inversus and Truncus Arteriosus - Swapnil Moharkar; Alpa Bharati (Indian Journal of Radiology and Imaging, 2023)
Congenital anomalies of the coronary arteries are rare. In this article, we reported a case of 6-month-old female who was brought with breathing difficulty and poor weight gain. Echocardiography was done which showed dextrocardia and truncus arteriosus. A cardiac computed tomography confirmed these findings and additionally revealed that the coronary arteries originated from a common vascular channel from the brachiocephalic artery. This is a very rare occurrence. To our knowledge, only a few such cases have been reported in the literature.